Learning in medical colleges: then and now - Pandya, Sunil K (Research and Humanities in Medical Education, 2014)
Great changes have taken place in medical education in India over the past 50 years. In the medical colleges of yesteryears, pioneers and inspiring teachers made the study and practice of medicine meaningful. The competition for post-graduate studies was far less intense and students spent substantial time in the wards, and with patients. In contrast, the intense struggle to enroll in desired specialties has resulted in great importance being placed on the development of short-term memory. Deeper understanding of the subject is given short shrift. The implications of these trends on patient care are obvious. Students are not exposed to the humanities for â€œwant of timeâ€ due to massive syllabi and this inturn leads to physicians who are trained with very little or no exposure to the discussion of human suffering that accompanies disease.